An optimization framework to identify key management strategies for improving biorefinery performance: a case study of winter barley production. (15th September 2020) - Kar, Saurajyoti; Riazi, Bahar; Gurian, Patrick L.; Spatari, Sabrina; Adler, Paul R.; Parton, William J.
Abstract: The selection of locations and practices for energy crops requires the economics to be planned and the carbon intensity of the fuel to be assessed. This study develops a framework for selecting near‐optimal cropland sites to minimize the cost to produce a targeted quantity of an energy crop, considering soil properties, fertilizer management, and spatio‐temporal trends in crop yield and soil emissions. DayCent, a biogeochemical model, simulates site‐level crop yield, and soil emissions. As a case study, this framework is applied to a 2.08 × 10 8  L year −1 capacity barley‐to‐ethanol biorefinery that selects cultivation sites from winter fallow cropland in the mid‐Atlantic region of the USA. The framework implements carbon crediting as per California's Low Carbon Fuel Standard. Our analysis finds the biorefinery's strategy on co‐products significantly influences its life‐cycle carbon intensity ranging between 0.74 gCO2 e MJ −1 for all co‐product use and 59 gCO2 e MJ −1 for no co‐product use. Coastal counties in Delaware show low soil emission and high yield, but higher transportation distances increase the carbon intensity of these distant croplands. When co‐products are used, the least intensive fertilizer management with fertilizer applications in spring is identified as the cost‐optimized choice for the biorefinery. It is also the option economically favored by growers, suggesting that detailed monitoring of these practices might not be needed to assure the adoption of low‐emission cultivation practices. However, the framework might demonstrate different results for other biofuel‐crop scenarios or different locations. The framework presented can assess the performance of a biorefinery prospectively and improve investors' confidence in the biofuel industry. © 2020 Society of Chemical Industry and John Wiley & Sons, Ltd.